High-definition transcranial direct current stimulation of the lateral occipital cortex influences figure-ground perception. (14th May 2021) - Sasia, Brooke; Cacciamani, Laura
Abstract: Prior work has shown that the lateral occipital cortex (LO) is involved in recognition of objects and their parts, as well as segregation of that object (or "figure") from its background. No studies, though, have examined how LO's functioning is influenced by non-invasive brain stimulation, particularly during a figure-ground perception task. The present study tested whether high-definition transcranial direct current stimulation (HD-tDCS) to right LO influences the effects of familiarity on figure-ground perception. Following 20 min of offline anodal stimulation (or sham), participants viewed masked stimuli consisting of two regions separated by a vertical border and were asked to report which region they perceived as figure. One region was the "critical" region, which either depicted a portion of a familiar object ("Familiar" stimuli), or a familiar object with its parts rearranged into a novel configuration ("Part-rearranged" stimuli). Previous research using these stimuli has found higher reports of the critical region as figure for Familiar vs. Part-rearranged displays, demonstrating the effect of familiarity on figure assignment. The results of the current study showed that HD-tDCS to right LO significantly influenced this typical behavioral pattern. Specifically, stimulation (vs. sham) increased reports of the critical region as figure for Part-rearranged stimuli, bringing perception of these displays up to the level of the Familiar stimuli. We interpret this finding as evidence that stimulation of right LO increased participants' reliance on the familiarity of the parts in their figure-ground judgements—a finding consistent with and extending previous research showing that LO is indeed sensitive to object parts. This is the first study showing that HD-tDCS to LO can influence the effects of familiarity on figure-ground perception. Highlights: Anodal high-definition tDCS was applied to the lateral occipital cortex (LO). Participants performed a figure assignment task with bipartite displays. Figure-ground displays depicted familiar or part-rearranged objects. tDCS (vs. sham) influenced the effects of familiarity on figure assignment. Results speak to the role of LO in figure-ground perception.